Gambaran Kadar Trigliserida Pada Mahasiswa Penikmat Seblak di Kampus Stikes Karsa Husada Garut - Sugiah Sugiah; Aceng Ali Awaludin; Lia Mar’atiningsih; M. Hadi Sulhan; Gina Nafsa Mutmaina; Mamay Mamay; Astari Nurisani; Meti Rizki Utari; Dendi Leona (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Seblak is a typical food or culinary dish from the city of Bandung, West Java, derived from the words segak and nyegak which mean stinging with a composition consisting of chewy crackers sautéed in onion-spiced sauce, which is sometimes added with sausage, eggs, sliced ​​vegetables, meatballs, shrimp, squid. and others. This study aims to determine the description of triglyceride levels in seblak connoisseurs at the STIKes Karsa Husada Garut Campus. The research design used in this study was descriptive in nature, the GPO-PAP examination method with the measurement results in the form of triglyceride levels in mg/dl. This measurement scale is included in the ordinal measurement scale. The research was conducted at the Karsa Husada Garut STIKes Clinical Chemistry Laboratory in June 2023. Samples were obtained from venous blood of D3 Health Analyst students at STIKes Karsa Husada Garut. The definition of student in the Big Indonesian Dictionary (KBBI) is a student who studies at a university. Students' eating habits are determined by culture, lifestyle, beliefs and the environment in which the community lives. Increased triglyceride levels (hypertriglyceridemia) is one part of dyslipidemia which is the main factor causing coronary heart disease. Hypertriglyceridemia has a role in causing coronary heart disease. Based on the average results obtained, it can be concluded that the research results depict triglyceride levels in students of consuming seblak at STIKes Karsa Husada Garut campus, most of the respondents had normal triglyceride levels.